SENSITINS FOR DIFFERENTIATING NONSPECIFIC REACTIONS TO PPD TUBERCULIN MAMMALIAN IN CATTLE - M. Bazarbaev; N. S. Syrym; S. Z. Basybekov; A. K. Mussayeva; S. G. Kanatbayev; C. M. Romashev; A. K. Dossanova; D. R. Sadikova; A. T. Mankibaev; B. A. Yespembetov (Journal of Animal and Plant Sciences, 2017)
The paper presents the study of the habitat of mycobacteria in various natural and climatic zones of the Karaganda region, which showed that out of all the isolated cultures, 307 (94.5%) were atypical mycobacteria (М. scrofulaceum, M. avium). At that, 64.5% of atypical mycobacteria cultures (М.scrofulaceum, M. avium) were isolated from the diagnostic material and objects of the external environment of the steppe zone.Thesensitinsfrom epizootic strains of mycobacteria were tested in terms of such criteria as sterility, safety, reactogenicity, lack of sensitizing properties, activity, and specificity. The sensitinswere administered to guinea pigs and cattle using an intradermal needless syringe. Preliminary experiments on guinea pigs found that sensitins had biological and specific activity, identical to avian purified protein derivative tuberculin. The tests of developed sensitinsМ. Scrofulaceumand M. avium on 59 cattle showed that the sensitins were highly effective in differentiating nonspecific reactions and demonstrated the expedience of their application.Using sensitins for lifetime differentiation of nonspecific reactions to tuberculin mammalian in healthy animals and cattle recovering from tuberculosis prevents the premature slaughtering of commercially valuable animals of a reproductive age.
Keywords: atypical mycobacteria; cattle; mycobacteriosis; sensitins; tuberculosis